Correction: Unexpected surface interactions between fluorocarbons and hybrid organic inorganic perovskites evidenced by PM-IRRAS and their application towards tuning the surface potential. Issue 1 (7th December 2018) - Sadhu, Subha; Aqueche, Kyler; Buffeteau, Thierry; Vincent, Jean-Marc; Hirsch, Lionel; Bassani, Dario M.
Abstract : Correction for 'Unexpected surface interactions between fluorocarbons and hybrid organic inorganic perovskites evidenced by PM-IRRAS and their application towards tuning the surface potential' by Subha Sadhu et al., Mater. Horiz., 2019, DOI: ;10.1039/c8mh01119b .